Polite rhetoric: Judah's plea to Joseph in Genesis 44.18-34. (June 2019) - Bridge, Edward J
Despite recognition that Judah's plea to the unknown-to-him Joseph in Gen. 44.18-34 is one of the most tactful yet moving pleas in the Hebrew Bible, only Joosten's 2016 article has attempted to analyse why it is tactful yet persuasive. The present study uses a linguistic politeness analysis and interacts with Joosten's classical rhetorical approach to affirm much of Joosten's argument, yet also to argue that aspects of Joosten's argument can be better covered by linguistic politeness. Ultimately, how a biblical speech is worded pragmatically is as much about persuasive rhetoric as the content, and should be considered alongside other methods of analysis when biblical speeches are studied.